Western media propaganda towards Islam - The crisis of the Prophet’s cartoons - may God bless him and grant him peace - dahmani, ammar (Journal of Social Sciences and Humanities, 2021)
From the beginning of the problem of caricaturating the prophet Mohamed ( May Alla is peace and blessings be up on him ) by some Danish newspapers and before this, it was the bad declaration of the pope Benidict 16 where he accused Islam To be a religion of violence Adding To this, the bombings in paris and the U. S. All these events have made many boliticiams and decision makers to have a radical opinion and attitudes two and Moslims and Islam. These attitudes were interpreted by the hate of the west to Moslims and Islam in general and also towards the prophet Mohamed ( Mpbbh ) in particular What is the nature of these positions? What is its reality? What are its effects and repercussions? What is the strategy for confronting Western media propaganda towards Islam? And towards the Messenger, may God bless him and grant him peace?